PPARs in the Renal Regulation of Systemic Blood Pressure - Tamás Rőszer; Mercedes Ricote (PPAR Research)
Recent research has revealed roles for the peroxisome proliferator activated receptor (PPAR) family of transcription factors in blood pressure regulation, expanding the possible therapeutic use of PPAR ligands. PPARα and PPARγ modulate the renin-angiotensin-aldosterone system (RAAS), a major regulator of systemic blood pressure and interstitial fluid volume by transcriptional control of renin, angiotensinogen, angiotensin converting enzyme (ACE) and angiotensin II receptor 1 (AT-R1). Blockade of RAAS is an important therapeutic target in hypertension management and attenuates microvascular damage, glomerular inflammation and left ventricular hypertrophy in hypertensive patients and also show antidiabetic effects. The mechanisms underlying the benefits of RAAS inhibition appear to involve PPARγ-regulated pathways. This review summarizes current knowledge on the role of PPARs in the transcriptional control of the RAAS and the possible use of PPAR ligands in the treatment of RAAS dependent hypertension.